The Relation between Maternal Work Hours and Primary School Students’ Affect in China: The Role of the Frequency of Mother–Child Communication (FMCC) and Maternal Education - Zhou, Huan; Lv, Bo; Guo, Xiaolin; Liu, Chunhui; Qi, Bing; Hu, Weiping; Liu, Zhaomin; Luo, Liang (Frontiers in Psychology, 2017)
Background: Although substantial evidence suggests that maternal work hours may have a negative effect on children’s cognitive development, the link between maternal work hours and children’s affect remains unclear. Some studies have observed that non-daytime maternal work hours are associated with more emotional problems among children. However, few studies have focused on the effects of maternal work hours on workdays and non-workdays. Therefore, this study separately investigated the relation between maternal work hours on workdays and on non-workdays and explored the mediating role of the frequency of mother-child communication (FMCC) and the moderating role of maternal education. Method: Using cluster sampling, this study selected 879 students in grades 4-6 at two primary schools in the Hebei and Shandong provinces in China and their mothers as the study subjects. A multi-group structural equation model (SEM) was used to test the relations between maternal work hours, FMCC and children’s affect and the moderating effect of maternal education. Results: (1) Non-college-educated mothers’ work hours on workdays negatively predicted FMCC, but there was no such effect for college-educated mothers; (2) non-workday work hours of all employed mothers negatively predicted FMCC; (3) the FMCC of all employed mothers positively predicted children’s positive affect; (4) the FMCC of college-educated mothers negatively predicted children’s negative affect although there was no such relation for non-college-educated mothers; (5) there was a significant mediating effect of FMCC on the relation between maternal work hours and children’s affect only for non-college-educated mothers; and (6) the workday work hours of non-college-educated mothers positively predicted children’s negative affect, but this correlation was negative for college-educated mothers. Conclusion: Maternal work hours have a marginally significant negative effect on children’s affect through FMCC only for non-college-educated mothers. Compared with non-college-educated mothers, college-educated mothers more easily compensate for the loss of communication opportunities caused by increased work hours on workdays, and children with college-educated mothers benefit more from this communication. However, compensating for the loss of communication opportunities caused by increased work hours on non-workdays is difficult for all employed mothers.